The role of professor M. Reusner in preparing of the Decree on the separation of church from state and school from church - Pavel Isakov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article deals with one of the key events in the history of relations between the state and religious denominations in Russia, i.e. preparing the decree on the separation of the church from the state and the school from the church. This decree determined the main principles and directions of activities of the state as to the church. The article shows the role of M.A. Reusner, the prominent scholar and lawyer, in the preparation of the decree, identifi es his actual role in the process of designing the document. Using documentary materials and academic works of Prof. M.A. Reusner himself, the article analyses his contribution to the development of the decree. The article also assesses the historical role of the scholar in the committee which prepared the decree as well as the influence of his expert and personal opinions on the formulation of specifi c provisions of the decree. The main conclusion of the study is that Prof. Reusner, who was a renowned scholar and lawyer involved in the work of the decree was not its actual ideologist.